Letramento digital e formação de professores : práticas docentes com a ferramenta interativa Jamboard - Aires, Ângela Maria Leite (2022)
With this, our society experiences challenges, experiences, innovations and new social practices that reflect directly on people and their ways of relating. In the educational context it is no different, based on the assumption that 21st century education is experiencing a new scenario of insertion of contemporary digital technologies, it is necessary to adapt our curriculum and our pedagogical practice to this scenario full of methodologies and ways to facilitate learning . With this in mind, our research will be developed with a view to the insertion of technologies in the context of teacher training, following the paths of digital literacy, which allows the subject to read and write according to verbal and non-verbal codes using technological tools. To carry out our study, we will use the interactive tool Jamboard in order to support teachers and promote interactive learning between students and teachers involved, thus generating mediated teaching through an active learning methodology. The general objective: To analyze the use of TIDICs by teachers in the municipality of Santo André-PB, as a tool in the teaching-learning process. The specific objectives are: To investigate the effect of technological tools, especially Jamboard, in helping the teaching practice in the teaching-learning process; to find out if the education network offers continuing education to teachers in the face of technologies in teaching; identify which technological tools the school offers to favor the work of teachers and propose a plan that aims to provide a continuous education focused on the use of the tool as a proposal for digital literacy. The project will be developed with elementary school teachers from a municipal school located in the city of Santo André-PB. The qualitative research is based on the collaborative ethnographic approach with emphasis on teacher training and teaching practice investigating the use of Digital Information and Communication Technologies -TDICs. Data collection will be based on the information obtained through the questionnaires sent via Google form and continuing education plan with the teachers involved. To support the research, we will use the contributions of Almeida (2007), Jacques Delors et al (1998), Kenski (2012), Libâneo (2011), Lowry et al. (2004), Melo and Santos (2021), Moran (2013), Moreira (1999), among others that guide our work with discussions on education mediated by technological tools in the classroom, literacies and teacher training. We reinforce that the interactive and transversal production of Jamboard, encompassing students and teachers, mobilizes competences and capacities for action, raises collective intelligence practices. We conclude that the school does not provide technological devices so that work can be carried out with TDICs, possibly, this causes the lack of interest of teachers to form themselves in digital literacy and consequently insert it in their pedagogical practice.